(untitled) (Journal of Economic Research & Business Administration, 2016)
Currently, the development of competitive advantages of Kazakhstan’s economy in the long term can only be achieved on the basis of the transition to an innovative economy. A modern innovative economy as the fundamental basis of formation of national innovation system, which is the basis for the functioning of the genesis of innovation as a non-uniform, non-linear and multifaceted process. Activating the innovation process is put into practice through the formation of national and regional innovation systems, in which the set of interrelations between various social and economic institutions for the development, deployment and diffusion of innovations. Innovative system of competitive countries of the world, for all their differences, are united in one thing: the process of genesis and implementation of innovation in these countries have high levels of efficiency and effectiveness. In Kazakhstan, the main elements of the national innovation system created in the last 10 years, but is dominated by an outdated idea of the linear model of innovation and an elementary chain to identify the effects of scientific and technological progress: the cost of science – the resulting increase in the absolute volume of sales.